2020
DOI: 10.1177/0300891620948961
|View full text |Cite
|
Sign up to set email alerts
|

The Severity of Acute Pancreatitis According to Modified Balthazar Classification in Patients With Pancreatic Cancer

Abstract: Objective: Although acute pancreatitis (AP) is a self-limited disease under supportive and medical treatment, it can have life-threatening potential in some patients. Results of studies reporting outcomes of AP-associated pancreatic malignancy are controversial. The aim of this study was to evaluate the severity and prognosis of pancreatic cancer (PC)–related AP by modified Balthazar score. Methods: A total of 354 patients hospitalized and followed up in our clinic between 2013 and 2019 were included in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Finally, the RCA intervention model not only enhanced cooperation between medical staff, but also solved problems related to insufficient inspections and the low number of night shift nursing staff. Notably, following the RCA intervention, nursing staff training was strengthened, and a scientific scheduling system was formulated, which effectively reduced the occurrence of complications and improved patients' and their families' levels of satisfaction with nursing (20).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the RCA intervention model not only enhanced cooperation between medical staff, but also solved problems related to insufficient inspections and the low number of night shift nursing staff. Notably, following the RCA intervention, nursing staff training was strengthened, and a scientific scheduling system was formulated, which effectively reduced the occurrence of complications and improved patients' and their families' levels of satisfaction with nursing (20).…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 , 4 , 5 ] While mild and moderate pancreatitis affects only itself and adjacent organs locally, multiple organ failure may develop in severe pancreatitis due to both local and systemic effects. [ 1 , 3 , 4 , 8 ] It is known that morbidity and mortality decrease in patients with severe AP with early initiation of treatment and close monitoring. [ 18 ] For this reason, it is important to determine the course of the disease using laboratory and radiological parameters.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] While a life-threatening course is observed in 2–3% of the patients, the mortality can be up to 50% in severe AP. [ 3 8 ]…”
Section: Introductionmentioning
confidence: 99%
“…Other symptoms associated with PDAC such as poor appetite, diarrhea or loose stool secondary to steatorrhea, unintentional weight loss, and recent or new-onset diabetes, should raise the concern for malignancy in patients presenting with acute pancreatitis [42]. Although studies have reported that most PDAC-AP patients present with mild acute pancreatitis, based on clinical or imaging criteria for the classification of acute pancreatitis, in some patients, the presentation of PDAC-AP may be associated with severe necrotizing pancreatitis [7,43,[45][46][47][48].…”
Section: Clinical Manifestations Of Acute Pancreatitis-associated Pan...mentioning
confidence: 99%